Isoquercetin and inulin synergistically modulate the gut microbiome to prevent development of the metabolic syndrome in mice fed a high fat diet - Tan, S.; Caparros-Martin, Jose; Matthews, V.; Koch, H.; O'Gara, Fergal; Croft, K.; Ward, Natalie (Nature Publishing Group, 2018)
Dietary fibre positively influences gut microbiome composition, enhancing the metabolism of dietary flavonoids to produce bioactive metabolites. These synergistic activities facilitate the beneficial effects of dietary flavonoids on cardiometabolic health parameters. The aims of this study were to investigate whether isoquercetin (a major dietary flavonoid) and inulin (soluble fibre), either alone or in combination could improve features of the metabolic syndrome. Following a 1 week acclimatization, Male C57BL6 mice (6-8 weeks) were randomly assigned to; (i) normal chow diet (n = 10), (ii) high fat (HF) diet (n = 10), (iii) HF diet + 0.05% isoquercetin (n = 10), (iv) HF diet + 5% inulin, or (v) HF diet + 0.05% isoquercetin + 5% inulin (n = 10). Body weight and food intake were measured weekly. At 12 weeks, glucose and insulin tolerance tests were performed, and blood, faecal samples, liver, skeletal muscle and adipose tissue were collected. At 12 weeks, mice on the HF diet had significantly elevated body weights as well as impaired glucose tolerance and insulin sensitivity compared to the normal chow mice. Supplementation with either isoquercetin or inulin had no effect, however mice receiving the combination had attenuated weight gain, improved glucose tolerance and insulin sensitivity, reduced hepatic lipid accumulation, adipocyte hypertrophy, circulating leptin and adipose FGF21 levels, compared to mice receiving the HF diet. Additionally, mice on the combination diet had improvements in the composition and functionality of their gut microbiome as well as production of short chain fatty acids. In conclusion, long-term supplementation with the dietary flavonoid isoquercetin and the soluble fibre inulin can attenuate development of the metabolic syndrome in mice fed a high fat diet. This protective effect appears to be mediated, in part, through beneficial changes to the microbiome.